Investigation of the relationships between mindfulness, wisdom, resilience and life satisfaction in Turkish adult population - EKŞİ, HALİL (My University, 2023)
There are many factors that are thought to affect life satisfaction. One of these factors is mindfulness. In addition, it has been observed that resilience and wisdom are associated with both mindfulness and life satisfaction. This study aims to examine the associations between mindfulness, resilience, wisdom, and life satisfaction. Participants consist of 1158 Turkish young adults (79.9% females) between the ages of 18 and 58 (Mage = 21.28, SD = 5.31). Mindfulness Scale, Brief Resilience Scale, San Diego Wisdom Scale, and Life Satisfaction Scale were used as the data collection tools. Structural Equation Modelling and Bootstrapping method were used to examine the role of resilience and wisdom in the relationship between mindfulness and life satisfaction. The results of the structural equation analysis showed that resilience and wisdom had a significant mediating role in the relationship between mindfulness and life satisfaction, and that the role of wisdom was stronger than resilience. The results of the bootstrapping analysis showed that the indirect effects of mindfulness on life satisfaction are significant. We conclude that mindfulness, accompanied by wisdom and resilience, can lead to an increase in life satisfaction. Theoretical and practical implications and limitations were discussed.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Social Sciences and Humanities; Psychology; Clinical Psychology; PSİKOLOJİ, KLİNİK; Temel Bilimler (SCI); PSYCHOLOGY, CLINICAL; PSYCHOLOGY; Natural Sciences (SCI); Klinik Psikoloji; Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; Mindfulness; Life satisfaction; Resilience; Wisdom; UNIVERSITY-STUDENTS; FIT INDEXES; IMPACT; DEPRESSION; STRATEGIES; BENEFITS; SCALE